Carbosilane dendrimers with phosphonium terminal groups are low toxic non-viral transfection vectors for siRNA cell delivery - Herma, Regina; Wrobel, Dominika; Liegertová, Michaela; Müllerová, Monika; Strašák, Tomáš; Maly, Marek; Semerádtová, Alena; Štofik, Marcel; Appelhans, Dietmar; Maly, Jan (International journal of pharmaceutics, 2019)
Non-viral gene delivery vectors studied in the gene therapy applications are often designed with the cationic nitrogen containing groups necessary for binding and cell release of nucleic acids. Disadvantage is a relatively high toxicity which restricts the in vivo use of such nanoparticles. Here we show, that the 3rd generation carbosilane dendrimers possessing (trimethyl)phosphonium (PMe3) groups on their periphery were able to effectively deliver the functional siRNA into the cells (B14, Cricetulus griseus), release it into the cytosol and finally to achieve up to 40% gene silencing of targeted gene (glyceraldehyde-3-phosphate dehydrogenase (GAPDH)) with the comparable or, in some cases, even better effectivity as their ammonium counterparts. Moreover, such cationic dendrimers show relatively low in vivo toxicity as compared to their ammonium analogues when analyzed by standard fish embryo test (FET) on Danio rerio in vivo model, with LD50 = 6.26 μM after 48 h of incubation. This is more than 10-fold improvement as compared to published values for various other types of cationic dendrimers. We discuss the potential of further increase of the transfection efficiency, endosomal escape and decrease of toxicity of such non-viral vectors, based on the systematic screening of different types of substituents on central phosphonium atom.
Keywords: Zebrafish; buněčné linie; RNA, Small Interfering; dánio pruhované; Dendrimers; Cell Line; umlčování genů; Organophosphorus Compounds; transfekce; Lethal Dose 50; Cricetulus; embryo nesavčí; Embryo, Nonmammalian; organofosforové sloučeniny; zvířata; Gene Silencing; malá interferující RNA; LD50; Animals; dendrimery; Silanes; silany; Transfection